Exploring history and memory through autobiographical memory - Goodson, Ivor (Historia y Memoria de la Educación, 2015)
The article reviews the role of autobiographical memory as a site of narrative construction. Far from being a place of liberal retrospective recall it is a site of active recapitulation and reconstruction. The article provides examples of how history and memory are intermingled. It also draws in the author’s autobiographical vignettes to explore the underpinning desires for historical reconstruction in autobiographical memory work